Revising the Historiography of Russian Church Music, or Myths and How to Debunk Them - Harri Jopi (Finland, 2022)
The paper addresses certain issues of the “established” historiography of Eastern Slavic church music that appear as illogical, and for that reason, suspicious. A matter that has been greatly neglected in the “classical” research is the creative role of the practising church musician, not as the composer but as the performer. By a closer inspection of primary sources and an approach more versatile than what has been traditional, revised interpretations are proposed.
Creating Liturgically: Hymnography and Music: Sixth International Conference on Orthodox Church Music